Social Construction of Human Trafficking in Canada: Diagnostic and Prognostic Framing of Anti-Trafficking Efforts at the Federal Government Level - Simonovska, Tijana (Université d'Ottawa / University of Ottawa, 2019)
Human trafficking is a societal phenomenon that has received much recognition both in Canada and in the international community in the last decade. This thesis applies a social constructionist theoretical lens to explore how human trafficking is described and understood at the federal government level in Canada. Specifically, this thesis observes how Parliamentary Committees construct human trafficking through the application of claims-making and framing strategies when discussing anti-trafficking efforts at the federal government level. The findings indicate that although there are ideological differences noted in how the issue is discussed, human trafficking has largely been constructed as a social problem that requires a criminal justice response. This thesis points to the challenges and unintended harms that stem from framing human trafficking through the lens of criminalization by exploring the issues that arise from adopting solutions which are not representative of the complex lived experiences of affected populations and in turn misconstrue the ways to manage the issue in the Canadian societal context.
Keywords: Human trafficking in Canada; Social construction theory; Claims-making and framing strategies; Parliamentary Committees; Content analysis